Photoperiod response in 1200 lines of beans tested at CIAT- Palmira 1982-3 : A listing - Gniffke, PA (International Center for Tropical Agriculture, 1983)
Results are given of a survey to determine the photoperiod response (18 vs. 12.3 h) of 1261 bean lines during 1982 and the 1st half of 1983 at CIAT-Palmira. (CIAT)